Enhancing Pupils’ Interest In Reading In Indonesian Language Lessons Through Teachers’ Creativity In Year 4 At SDN 10 Mahikam - Yeni Yuliana; Aprima Tirsa; Indria Susilawati (CV PUTRA PUBLISHER, 2026)
The low reading interest of primary school pupils remains a persistent issue that affects their learning outcomes, particularly in Indonesian language learning. Reading skills serve as a fundamental foundation that determines pupils’ academic success. One strategic solution to address this problem is through teachers’ creativity in designing instruction. Creative teachers are able to create interactive, enjoyable, and experience-based learning environments that foster pupils’ motivation to read. This study aims to improve students’ reading interest through the implementation of creative teaching strategies in Year 4 at SDN 10 Mahakam. The method used was Classroom Action Research (CAR) based on the Kemmis and McTaggart spiral model, conducted in two cycles comprising planning, action, observation, and reflection. The research subjects were 14 students with varying reading abilities. The results showed an increase in learning implementation from 2.54 to 3.47 and in students’ reading interest from 2.47 to 3.57. It can be concluded that the application of creative teaching strategies effectively improves learning implementation and reading interest whilst fostering an independent reading culture in the classroom.